2017
DOI: 10.2340/16501977-2168
|View full text |Cite
|
Sign up to set email alerts
|

Use of neuromuscular electrical stimulation to preserve the thickness of abdominal and chest muscles of critically ill patients: A randomized clinical trial

Abstract: Objective: To evaluate and compare the effects of neuromuscular electrical stimulation combined with conventional physical therapy on muscle thickness in critically ill patients. Design: Double-blind, randomized controlled trial. Patients: Twenty-five patients participated in the study. Methods: Patients on mechanical ventilation for 24-48 h were randomized to an intervention group (neuromuscular electrical stimulation + conventional physical therapy) or a conventional group (sham neuromuscular electrical stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
2
19
1
2
Order By: Relevance
“…For the pooled data, we observed a between-group difference in total abdominal expiratory muscle thickness changes on day 3, favoring the active group. Although effects were small, our observations are in line with Dall’Acqua et al [ 28 ], showing that FES of the rectus abdominis muscle (note that this muscle is to a limited extent involved in expiration [ 1 ], therefore not specifically targeted in our study) of ICU patients resulted in muscle mass preservation in the active group, while thickness decreased in the sham group. However, we found no between-group differences on day 5, likely resulting from insufficient sample size and observer variability (see ‘ Strengths and limitations ’ section).…”
Section: Discussionsupporting
confidence: 91%
“…For the pooled data, we observed a between-group difference in total abdominal expiratory muscle thickness changes on day 3, favoring the active group. Although effects were small, our observations are in line with Dall’Acqua et al [ 28 ], showing that FES of the rectus abdominis muscle (note that this muscle is to a limited extent involved in expiration [ 1 ], therefore not specifically targeted in our study) of ICU patients resulted in muscle mass preservation in the active group, while thickness decreased in the sham group. However, we found no between-group differences on day 5, likely resulting from insufficient sample size and observer variability (see ‘ Strengths and limitations ’ section).…”
Section: Discussionsupporting
confidence: 91%
“…A total of 693 related studies were identified in the preliminary search, and 11 RCTs [ 13 , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ], including 576 patients, were finally included. A flow chart detailing the article screening process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“… Acqua et al. [ 26 ] 2017 Brazil 19/19 ≥18 years of age, ≥24 h of MV duration and ≥15 days of total length of stay. NMES False NMES + routine care 30 min per day and 1 min was added every 2 days of administration; 50 Hz frequency, pulse duration 300 ms, rise time 1sec, stimulus time (on) 3sec, deck time 1sec, and relaxation time (off) 10 sec.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations